Prophetic Law in Modern Business: Integration of Humanization, Liberation, and Transcendence in Commercial Contracts - Disantara, Fradhana Putra; Ishwara, Ade Sathya Sanathana; Disantara, Geraldha Islami Putra; Abdunayimova, Dinara (Batulis Civil Law Review, 2025)
Introduction: Economic globalization has significantly influenced the practice of business law, particularly commercial contracts that are increasingly complex, cross-border in nature, and dominated by capitalist interests. Contracts, which ideally serve as instruments of justice, often function as tools of domination by stronger parties over weaker ones, thereby neglecting humanitarian, ethical, and spiritual dimensions.Purposes of the Research: The purpose of this research is to analyze how the principles of prophetic law can be integrated into modern commercial contract practices and to identify the challenges arising in the era of globalization.Methods of the Research: This study employs normative legal research with a conceptual approach, examining the principles of prophetic law and linking them to contemporary business law practices. The data were analyzed qualitatively through a review of legal literature, philosophical discourse, and modern commercial contract practices.Results Main Findings of the Research: The findings indicate that the principle of humanization plays a crucial role in restoring contracts to their human dignity by protecting weaker parties; the principle of liberation calls for the elimination of exploitative contractual practices; while the principle of transcendence stresses the necessity of embedding ethical and spiritual values in business. The challenges of integration include the dominance of global capitalism, rigid digital contract frameworks, and the weak moral awareness of business actors. The originality of this study lies in its systematic effort to connect prophetic law with modern commercial contract practices, thereby offering a new paradigm for global business law that is more just, humane, and sustainable.